In the circumstances about poems and poets - Robinson, Peter 1953- (Clarendon Pr., 1992)
In the Circumstances is a study of the way people other than their authors contribute to poems. Discussing work by Wordsworth, Browning, Hardy, Pound, Eliot, Montale, Auden, Lowell, and Hill, the book explores how other people's lives and wider circumstances can influence the textual contexts of poems and be felt within the works themselves. These circumstances emerge in such things as allusions to political events of the day, the inclusion of proper names and, above all, the citation or absorption of the words of others. The book asks how the poets themselves worked these circumstances into the fabric of their poems, and what bearing this has on subsequent acts of revision and translation. These are current issues: for all those involved with poetry, as readers or writers, this book will provide pleasure and stimulus.
Keywords: Geschichte 1789-1992; Geschichte 1900-1992; Geschichte 1800-1970; Dichtkunst; Leesgewoonten; Receptie; Rezeption; Authors and readers; Poetry -- History and criticism; Reader-response criticism; Englisch; Literaturpsychologie; Lyrik; USA